Are Prospective Counsellors Able to Listen Emphatically? (A Study among Counselling University Students in Indonesia) - Dedy Surya (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2021)
Listening ability determines the success of counselling sessions. Counsellors must be able to listen to the various problems presented by their participants wholeheartedly. This research aims to illustrate the ability of emphatic listening among counselling students in Indonesia. This descriptive quantitative study involved 318 participants (88.7% women) aged 18-23 years (M= 19.24, SD=1.108) voluntarily selected through convenience sampling. The emphatic listening skills were measured using The Active-Emphatic Listening Scale by Bodie (2011) using Google Form. Based on statistical analysis, it was found that empathic listening to counselling students was classified as high. The study also argues that there are differences in empathy listening skills based on the environment in which they live. At the same time, differences in sex, age, and study year did not determine differences in listening empathetically. This study confirmed that the environment in which a person grows up has implications for empathy.